Ecogreen Peritoneal Dialysis Waste Disposal System: A Case Study from The Public Health Nursing Perspectives - Tukayo, Isak Jurun Hans; Afzal, Ridha; Korompis, Martha Debora; Hardy, Syaifoel; Kuswandari, Shanti; Maulana, David (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: The increased amount of Peritoneal Dialysis (PD) medical waste will harm the environment and humans around it, and so far there is no system. Many studies revealed more about how to handle medical waste. This study aims to identify hazardous and non-hazardous medical waste and to introduce an environmentally friendly PD disposal system.Methods: This research was a case study method with a descriptive design. The population and sample of PD waste were 40 patients in PD in South Sulawesi (n: 19) and Manado, North Sulawesi (n: 21), Indonesia. The instrument used was a document review with the PICO model as a filter. The instrument was used to filter reliable research documents obtained from Google Scholar for the last 5 years (2017-2022), with keywords: peritoneal dialysis, medical waste disposal, CAPD nurses. Nightingale’s Environment Theory was also used to support the analysis.Results: Collected 177 grams of PD medical waste or an average of 620 grams a day with a risk load of 6 out of 7 items. In a month, 18.6 kgs of PD medical waste will be collected. The waste is mixed (hazardous and non-hazardous) and potentially dangerous.Conclusion: This study recommended a disposal system that is not yet clear and there is no certainty about who is in charge. The combustion results can be used for ecogreen plant fertilizers where in its application it can involve public health nursing because of their close role in family and community health.